Non-calcifying variant of calcifying epithelial odontogenic tumor with clear cells-first case report of an extraosseous (Peripheral) presentation - Afroz, Nishat; Jain, Anshu; Maheshwari, Veena; Ahmad, Syed Saeed (European Journal of General Dentistry, 2013)
Calcifying epithelial odontogenic tumor or Pindborg tumor is a rare benign odontogenic tumor that was first described by a Danish pathologist Jens Jorgen Pindborg in 1955. It is thought to arise from the epithelial element of the enamel origin and is histologically characterized by the presence of polygonal epithelial cells, amyloid globules, and Liesegang ring calcifications. A few cases have been shown to demonstrate clear cells (Langerhans cells) in the tumor. Non-calcifying epithelial odontogenic tumor (NCEOT) s very rare and only four cases have been documented in the English Language Literature to date. All these cases were present intraosseously (central). We present the first case of an extraosseous (peripheral) NCEOT with clear cells (Langerhans cells) and briefly discuss as well as review the histogenesis along with the differences in its clinicopathological and prognostic profile with respect to other variants.
Keywords: Calcifying epithelial odontogenic tumor; clear cells; extraosseous; langerhans cells; non-calcifying; peripheral